2017
DOI: 10.1016/j.jcis.2016.10.084
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte solution structure and its effect on the properties of electric double layers with surface charge regulation

Abstract: The physical origin of charged interfaces involving electrolyte solutions is in the thermodynamic equilibrium between the surface reactive groups and certain dissolved ionic species in the bulk. This equilibrium is very strongly dependent on the precise local density of these species, also known as potential determining ions in the solution. The latter, however, is determined by the overall solution structure, which is dominated by the large number of solvent molecules relative to all solutes. Hence, the solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…27 For pH values much greater than 2, silica presents numerous negative sites at its surface, so that cationic counterions are attracted whereas anionic co-ions are repelled. This distribution and the random thermal motion of ions lead to formation of an electric double layer 11,28 with an inner layer rich in cations and a diffuse layer where cations and a majority of anions are present, this has to be noted. Far away from the surface, the number density of counterions and co-ions is the same to satisfy electroneutrality.…”
Section: Resultsmentioning
confidence: 99%
“…27 For pH values much greater than 2, silica presents numerous negative sites at its surface, so that cationic counterions are attracted whereas anionic co-ions are repelled. This distribution and the random thermal motion of ions lead to formation of an electric double layer 11,28 with an inner layer rich in cations and a diffuse layer where cations and a majority of anions are present, this has to be noted. Far away from the surface, the number density of counterions and co-ions is the same to satisfy electroneutrality.…”
Section: Resultsmentioning
confidence: 99%
“…The electrolyte solution is described in terms of a grand thermodynamic potential functional, which for single flat EDL reads [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ] …”
Section: The Grand Thermodynamic Potentialmentioning
confidence: 99%
“…This approach includes the contributions of the interactions between the solutions species, which are present in the terms [ 21 , 22 ], which accounts for the excluded volume effects and , which captures long-range interactions. In our model, these interactions are of the Lennard-Jones (LJ) [ 25 ] and Coulombic type [ 14 , 17 , 18 , 19 , 20 ], where , is the diameter of component “ i ” and is the distance between species “ i ” and “ j ”. All non-Coulombic interactions of a molecule (or ion) of type “ i ” with the interface are assumed to be of the “hard wall” type, that is, only the excluded volume effects are taken into account.…”
Section: The Grand Thermodynamic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lee et al [169] found that various physical quantities that depend on the orientation of solvent molecules were not accurately predicted by the primitive model approach. Additionally, Vangara et al [170] recently showed, by comparing explicit and implicit solvent DFT models, that both the solvent and the ions contribute to the chemical balance between surface groups and the solution.…”
Section: Latest Developments In Molecular Modelingmentioning
confidence: 99%